SYNTHESIS, CHARACTERIZATION AND PERFORMANCE OF CNTsSUPPORTED BIMETALLIC NANOCATALYSTS IN FISCHER-TROPSCH REACTION - ALI, SARDAR (2012)
Fischer-Tropsch Synthesis (FTS) is a very important process which deals with the chemical conversion of synthesis gas into hydrocarbons and oxygenates with a broad range of chain lengths and functionalities. FTS has a potential to produce liquids fuels and chemicals from a variety of chemical feedstocks such as natural gas, coal and biomass. Industrially alumina (Ab03) and silica (Si02) supported cobalt (Co) based are extensively used. There are some problems associated Co-based catalysts supported on conventional metal oxides such as metal-support mixed oxide formation, sintering. lower reducibilties and dispersion. The objective of this project was to synthesize. characterize and evaluate the performance of CNTs-supported bimetallic nanocatalysts in a Fischer-Tropsch Synthesis (FTS). The bimetallic nanocatalyst systems consisted of Co-Fe, Co-Mn and Co-Mo. A total metal loading of 5 weight % and various formulations (Co/CNTs, 70Co30M/CNTs, 50Co50M/CNTs. 30Co70M/CNTs and M/CNTs) have been synthesized using a wet impregnation method on CNTs support. The effects of promoters such as potassium (K), niobium (Nb), copper (Cu) and platinum (Pt) at various levels, on the physicochemical properties of the nanocatalysts have been investigated. The physicochemical properties of the nanocatalysts were investigated using N2 physical adsorption, field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), CO-chemisorption, hydrogen temperature-programmed desorption (H2-TPD), temperature-programmed oxidation (TPO), carbon dioxide temperature-programmed desorption (COr TPD) and hydrogen temperatureprogrammed reduction (H2-TPR). The performance of all the synthesized catalysts in FTS was investigated in a fixed-bed microreactor at atmospheric pressure and various feed ratios of the reactants (H2/CO). temperature, and space velocity while selected nanocatalysts were investigated at 20 bar.